Pengaruh Pembiayaan bagi Hasil terhadap Profitabilitas Unit Usaha Syariah (UUS) di Indonesia - Mujib, Muhamad; Ilmiyah, Izzatul (Journal of Islamic Finance and Syariah Banking, 2024)
This research aims to see the correlation and influence of profit-sharing financing on the profitability of Sharia Business Units (UUS) in Indonesia. The dependent variable in this Research is Return on Assets (ROA), while mudharabah and musyarakah financing are the independent variables. This research uses secondary data obtained from Sharia banking statistics, which are accessed via the Otoritas Jasa Keuangan (OJK) website. The data analysis technique used in the research is ordinary least squares (OLS). The results of this research show that mudharabah and musyarakah financing simultaneously (as a whole) have no effect on ROA. This is proven by the prob (F-statistic) value of 0.088620. The partial test results (t-test) show that mudharabah financing has a probability value of 0.3157, which makes mudharabah financing have no effect on ROA. Meanwhile, musyarakah financing has a probability value of 0.0353, so musyarakah financing has a significant influence on ROA.